1986
DOI: 10.1017/s003382220000761x
|View full text |Cite
|
Sign up to set email alerts
|

Dating of Holocene Stratigraphy with Soluble and Insoluble Organic Fractions at the Lubbock Lake Archaeological Site, Texas: An Ideal Case Study

Abstract: The Lubbock Lake site, on the Southern High Plains of Texas, contains one of the most complete and best-dated late Quaternary records in North America. A total of 117 14C dates arc available from the site, determined by the Smithsonian and SMU Laboratories. Of these dates, 84 have been derived from residues (humin) and humates (humic acids) of organic-rich marsh sediments and A horizons of buried soils. Most of the ages are consistent with dates determined on charcoal and wood, and with the archaeologic and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 17 publications
(11 reference statements)
2
54
0
Order By: Relevance
“…Radiocarbon ages were determined for soil organic matter (SOM) from buried soil horizons and organic-rich sediments, as well as charcoal (Table I). Although radiocarbon dating of organic-rich sediments is somewhat problematic (Martin and Johnson, 1995;Abbot and Stafford, 1996;McGeehin et al, 2001), studies have shown that with proper care in sampling and interpretation, these materials can provide good age control, especially in drier environments (e.g., Haas et al, 1986;Holliday et al, 1994Holliday et al, , 1996Quade et al, 1998;Rawling et al, 2003;Mayer and Mahan, 2004). The SOM samples underwent a standard acid-base-acid treatment to remove carbonate and isolate specific fractions of organic matter (after Abbot and Stafford, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Radiocarbon ages were determined for soil organic matter (SOM) from buried soil horizons and organic-rich sediments, as well as charcoal (Table I). Although radiocarbon dating of organic-rich sediments is somewhat problematic (Martin and Johnson, 1995;Abbot and Stafford, 1996;McGeehin et al, 2001), studies have shown that with proper care in sampling and interpretation, these materials can provide good age control, especially in drier environments (e.g., Haas et al, 1986;Holliday et al, 1994Holliday et al, , 1996Quade et al, 1998;Rawling et al, 2003;Mayer and Mahan, 2004). The SOM samples underwent a standard acid-base-acid treatment to remove carbonate and isolate specific fractions of organic matter (after Abbot and Stafford, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Prior to a few years ago, there were no radiocarbon ages from stratigraphically-controlled contexts anywhere in the Colorado drainage since the more traditional materials used for radiocarbon dating, such as charcoal, wood fragments, or other macrofossils, are rarely GEOARCHAEOLOGY, COLORADO AND CHONCHO RIVERS, WEST TEXAS preserved. In recent years radiocarbon laboratories have been assaying organic carbon contained in soil profiles and fine-grained sedimentary contexts with good results (Sharpenspeel, 1971;White and Valastro, 1984;Matthews, 1985;Haas et al, 1986). Based on past success with this technique (Blum, 1989;Blum and Valastro, 1989;Collins et al, 1990;Blum et al, 1992) radiocarbon ages for upper Colorado and Concho River deposits in the study area were obtained from bulk sediment and soil samples.…”
Section: Methodsmentioning
confidence: 99%
“…Radiocarbon ages from soil profiles, where some organic matter accumulated post-depositionally due t o pedogenic processes, are considered to represent a mean residence time for the organic carbon, and a minimum age for deposition of the host sediment (e.g., Sharpenspeel, 1971;Matthews, 1985). By contrast, radiocarbon ages from finely divided organic detritus in fine-grained sediments are assumed to represent the approximate time of deposition (Haas et al, 1986). All samples were processed at the Radiocarbon Laboratory of the University of Texas at Austin according to methods outlined in White and Valastro (19841, and assays are reported in uncorrected and uncalibrated 14C years before present (yr B.P.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, later studies determined that even the Lubbock Lake bison bone used to obtain C-558 almost certainly did not, in fact, come from the Folsom level at this site (Haas et al 1986;Holliday and Johnson 1986). The first 14 C age determination securely associated with Folsom materials was obtained on charcoal collected at the Lindenmeier site in Colorado.…”
Section: Chronological Placement Of Folsom (North America)mentioning
confidence: 96%